Visual Distractors Disrupt Audiovisual Integration Regardless of Stimulus Complexity - Gibney, Kyla D.; Aligbe, Enimielen; Eggleston, Brady A.; Nunes, Sarah R.; Kerkhoff, Willa G.; Dean, Cassandra L.; Kwakye, Leslie D. (Frontiers in Integrative Neuroscience, 2017)
The intricate relationship between multisensory integration and attention has been extensively researched in the multisensory field; however, the necessity of attention for the binding of multisensory stimuli remains contested. In the current study, we investigated whether diverting attention from well-known multisensory tasks would disrupt integration and whether the complexity of the stimulus and task modulated this interaction. A secondary objective of this study was to investigate individual differences in the interaction of attention and multisensory integration. Participants completed a simple audiovisual speeded detection task and McGurk task under various perceptual load conditions: no load (multisensory task while visual distractors present), low load (multisensory task while detecting the presence of a yellow letter in the visual distractors), and high load (multisensory task while detecting the presence of a number in the visual distractors). Consistent with prior studies, we found that increased perceptual load led to decreased reports of the McGurk illusion, thus confirming the necessity of attention for the integration of speech stimuli. Although increased perceptual load led to longer response times for all stimuli in the speeded detection task, participants responded faster on multisensory trials than unisensory trials. However, the increase in multisensory response times violated the race model for no and low perceptual load conditions only. Additionally, a geometric measure of Miller’s inequality showed a decrease in multisensory integration for the speeded detection task with increasing perceptual load. Surprisingly, we found diverging changes in multisensory integration with increasing load for participants who did not show integration for the no load condition: no changes in integration for the McGurk task with increasing load but increases in integration for the detection task. The results of this study indicate that attention plays a crucial role in multisensory integration for both highly complex and simple multisensory tasks and that attention may interact differently with multisensory processing in individuals who do not strongly integrate multisensory information.